Sintering-dissolution process for manufacturing ni-based superalloy foams - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2016)
In this work, porous Ni-718 and Nimonic-90 superalloy were produced by use of a water soluble pore forming agent prior to sintering. Carbamide particles were used as the space holder material. After compaction the space holder particles were extracted using warm water leaching over a range of temperatures. The porous green parts were subsequently thermally debound to remove the paraffin wax under a high purity Argon atmosphere, and subsequently sintered at high vacuum. The effects of volume fraction of space holder particles on density, porosity and compression strength were investigated. Microstructures were captured using optical and scanning electron microscopy.
Keywords: Ni-Based Superalloy; Porous Material; Powder Processing